PERSEPSI MAHASISWA UIN MALANG TERHADAP REPRESENTASI ANTI KEKERASAN DI DALAM BUKU ARABIYAH LIL HAYAH - Eka Prasetyo Nurdiansyah, Faiqotul Fauziyah, Siti Fu’aidatul Isma ‘Aini, Fakron Jamalin (PRODI PAI FIK UNIRA MALANG, 2025)
This study explores the values of anti-violence in the Arabic textbook Arabiyah Lil Hayah (ALH) and the perceptions of students at UIN Maulana Malik Ibrahim Malang regarding these values. The background of this research stems from the rising cases of violence in Indonesia's educational sector, highlighting the need for systematic efforts to cultivate student character that upholds peace and tolerance. One approach to achieving this is through textbooks that incorporate these values into their learning content. This research employs a qualitative method with a critical discourse analysis approach based on corpus linguistics. The data were obtained from two primary sources: the content of the ALH textbooks (volumes 1 to 4), analyzed using AntConc software, and the results of a Focus Group Discussion (FGD) involving 104 first-semester students participating in the Special Arabic Language Development Program (Program Khusus Pengembangan Bahasa Arab or PKPBA). The findings show that the ALH textbooks explicitly and implicitly convey anti-violence messages through narratives, dialogues, and illustrations depicting peaceful conflict resolution, the importance of consultation (musyawarah), and the exemplary character of the Prophet Muhammad (PBUH) in dealing with differences. Students' perceptions of these values were very positive; they emphasized the importance of dialogue-based approaches, polite communication, and respect for others' rights in social life. This study demonstrates that textbooks play a significant role in instilling anti-violence character in students. However, the scope of the study is limited to indicators of religious moderation and a single institution. Therefore, future research is recommended to expand the sample and examine other indicators, such as tolerance and national commitment.